Chinese Dream and Practice in Zhejiang - Society - Chen, Guangjin; Yang, Jianhua; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2019)
The theme of this book is the society construction in Zhejiang Province under the guidance of "China Dream" policy. It adopts case studies, analysis, policy interpretations and practice summaries, presents the field practice and achievements in the local society. It exploits social studies areas such as social structure, public affairs management, urbanization, social security, as well as grassroots governance, society safety issues in the Zhejiang province. It also reveals a complete picture of the current society status in an analytical way. It helps scholars and political practitioners worldwide better understand how the "China Dream" policy has influenced the local Chinese society.
Chapter One The Change in Social Structure -- Chapter Two Urban-Rural Integration -- Chapter Three The Social Programs and Equal Access to Public Services -- Chapter Four Ensuring and Improving the People's Well-being -- Chapter Five Primary-level Social Governance -- Chapter Six Migrant Population Services and Management -- Chapter Seven The Building of a Safe Zhejiang -- Chapter Eight Zhejiang's Experience in Social Development and Inspirations.
Keywords: Sociology; Social sciences; Humanities; Developmental psychology; Sociology; Humanities and Social Sciences; Developmental Psychology